Analysis of Verticality Perception in Older Adults With and Without Acute Stroke in Half-Lying Versus Sitting Positions - Agostini, Lívia S.; Rodrigues, Priscila S. M.; Bazan, Rodrigo [UNESP]; Baggio, Jussara A. de Oliveira; Souza, Luciane A. P. S. de; Luvizutto, Gustavo J. (SAGE Publications, 2022)
Currently, there is no research consensus regarding the influence of body position on verticality perception in acute stroke. In this study, we aimed to compare the influence of half-lying and sitting positions on measurements of the subjective visual vertical (SVV) and the subjective haptic vertical (SHV) of individuals in the acute stroke phase. In this cross-sectional study, we compared these positional experiences in two groups of participants: adults in the acute stroke phase and elderly individuals without stroke. Independent variables were stroke versus no-stroke groups, in half-lying versus sitting positions. Analyzed variables of related interest were cognition (Mini-Mental State Examination or MMSE), stroke severity (National Institutes of Health Stroke Scale or NIHSS), and trunk control (Trunk Impairment Scale or TIS). Dependent variables were visual and haptic verticality, as evaluated by SVV and SHV. There were observed differences in absolute SVV in sitting position between groups (p = 0.021), absolute SVV in half-lying position between groups (p = 0.033), absolute SHV in sitting position between groups (p = 0.003), absolute SHV in half-lying position between groups (p = 0.002), and constant SVV in half-lying position between groups (p = 0.007). In the stroke group there was a higher coefficient of variation of SVV and SHV in the half-lying position compared to sitting position. In the sitting position, we observed a very strong correlation between the TIS and absolute SHV (p = 0.008). We concluded that individuals in the acute phase of stroke had greater misperceptions of visual and haptic verticality than older adults without strokes and that individuals in the acute phase of stroke showed less variability in visual and haptic vertical perception in the sitting position than in the half-lying position. By implication, we should encourage the sitting position in the acute stroke phase and develop early strategies to increase the verticality perception.
Keywords: body self-perception; stroke; tactile perception; verticality; visual perception